Bailout bypass surgery for complications of coronary interventions. (May 2020) - Szczechowicz, Marcin P.; Mkalaluh, Sabreen; Torabi, Saeed; Zhigalov, Konstantin; Mashhour, Ahmed; Karck, Matthias; Easo, Jerry; Weymann, Alexander
Background: Mechanical complications of percutaneous coronary interventions are treated percutaneously in most cases. If the rescue intervention is unsuccessful, bailout bypass surgery is necessary to restore the coronary flow. The surgical risk in these cases is higher than that of patients operated on for other indications. The aim of our study was to characterize patients who underwent surgical treatment at our institution and to compare their long-term outcomes with patients who underwent emergency bypass surgery for other indications. Methods: We analyzed 707 consecutive patients who underwent isolated emergency bypass surgery at our institution from 2007 to 2015. In 44 of these cases, the surgery was necessitated by mechanical complications of percutaneous coronary interventions. There were 31 coronary dissections, 5 entrapped guidewires, and 8 coronary perforations. We compared patients in these three groups with one another. Follow-up was performed to assess long-term outcomes. Results: The median age of the cohort was 68 years (range 59–75 years), and 36 (81.8%) patients presented in cardiogenic shock. Thirty-seven (84.1%) patients had history of a percutaneous coronary intervention. The courses were typical for bypass patients. The long-term survival was similar in all three subgroups ( p  = 0.16). The survival profiles within our sample did not differ significantly from that in patients who underwent emergency bypass surgery for other indications. Conclusions: Surgical risk and short- and long-term outcomes of patients undergoing emergency bypass surgery due to mechanical complications of percutaneous coronary interventions are similar to those of patients receiving the same surgery for other indications.